2022
DOI: 10.1155/2022/2071108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Field of View Size on CBCT Artifacts Caused by the Presence of Metal Objects in the Exomass

Abstract: Background and Aim. This study aimed to assess the effect of the size of the field of view (FOV) on cone-beam computed tomography (CBCT) artifacts caused by metal objects in the exomass. Materials and Methods. In this in vitro experimental study, titanium implants, teeth with cobalt-chromium (Co-Cr) intracanal posts, and teeth with mesio-occluso-distal (MOD) amalgam restorations were placed in an empty socket of the extracted third molar of a human mandible. These metallic materials were differently arranged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
5
1
Order By: Relevance
“…Another study evaluated the effect of presence of three titanium implants in the exomass using Cranex, 3Dx, Orthopos SL-3D, and XI scanners and reported a signi cant reduction in the mean GV compared with the control position [27]. Consistent with the present ndings, Sa et al [22] reported the highest reduction in the mean GV due to the presence of amalgam alloy, and the lowest reduction due to the presence of titanium implants in the exomass area.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Another study evaluated the effect of presence of three titanium implants in the exomass using Cranex, 3Dx, Orthopos SL-3D, and XI scanners and reported a signi cant reduction in the mean GV compared with the control position [27]. Consistent with the present ndings, Sa et al [22] reported the highest reduction in the mean GV due to the presence of amalgam alloy, and the lowest reduction due to the presence of titanium implants in the exomass area.…”
Section: Discussionsupporting
confidence: 84%
“…Using the smallest possible FOV has been recommended to protect against ionizing radiation and improve image quality [30,32]. However, in CBCT, reduction in size of FOV in the axial plane indirectly increases the exomass effect and occurrence of truncation [22,24,31,33], and heterogeneity in the reconstructed volume [34]. It should be noted that all previous studies on exomass artifacts used metal objects of the same volume and dimensions [11,15,16,27,28,35,36], which is different from the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated CBCT-related parameters in artefact generation, such as tube current (mA), field of view (FOV), tube voltage (kV) and CBCT unit-specific factors (Codari et al, 2017;Freitas et al, 2018;Pauwels et al, 2013;Safi et al, 2022;Sawicki et al, 2022;Schulze et al, 2010Schulze et al, , 2011Wanderley et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated CBCT‐related parameters in artefact generation, such as tube current (mA), field of view (FOV), tube voltage (kV) and CBCT unit‐specific factors (Codari et al, 2017; Freitas et al, 2018; Pauwels et al, 2013; Safi et al, 2022; Sawicki et al, 2022; Schulze et al, 2010, 2011; Wanderley et al, 2021). Artefact generation has been studied and related to the CBCT unit (Freitas et al, 2018; Vasconcelos et al, 2019; De Faria Vasconcelos et al, 2020), artefact‐generating material (Queiroz et al, 2018; Vasconcelos et al, 2019; De Faria Vasconcelos et al, 2020; Mancini et al, 2021), positioning (Vasconcelos et al, 2019) and scanning protocol (Freitas et al, 2018; Khosravifard et al, 2021; Mancini et al, 2021; Vasconcelos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%